Personal Characteristics and Job Satisfaction Among Nurses in Lebanon - Doumit, Myrna A.A. (2003)
Objective: This study investigates the level of satisfaction of Lebanese nurses in their job and the influence of their personal characteristics. Background: Given the current difficulties experienced by Lebanese hospitals in recruiting and retaining a sufficient number of nurses, the need to understand the reasons of nurses’ dissatisfaction became urgent. Moreover, satisfaction at work is essentially a personal experience also affected by cultural factors. Therefore, it was necessary to study the links between personal characteristics and nurses’ dissatisfaction. Methods: The study included 421 registered nurses. A modified version of Measure of Job Satisfaction, developed by Taynor and Wade, was used to assess the effect of the personal characteristics, namely educational level, age, years of work experience, position, and marital and parental status, on 5 dimensions of satisfaction: personal satisfaction, workload, professional support, pay and prospect, and training. Results: The findings suggest that personal characteristics have important influences on nurses’ job perceptions. University graduate nurses reported more dissatisfaction with the quality of supervision and with respect and treatment they receive from their superiors. Nurses younger than 30 years and the technically trained were more dissatisfied with the available opportunities to attend continuing education courses. Results of staff nurses and unmarried nurses showed trends of more dissatisfaction than the married and nurses of higher positions. Moreover, the whole sample perceived that nursing provided a high level of personal satisfaction, but nurses were most dissatisfied with salary and lack of prospects for promotion. Conclusion: The results indicate the importance of personal characteristics on nurses’ retention. Furthermore, intrinsic factors related to the nature and experience of nursing are more job satisfiers than extrinsic factors. Beirut, the capital of Lebanon, was called “the hospital of the Middle East” in the early 1970s because of its high level of medical and nursing care provided by its hospitals. Soon after the beginning of the civil war in 1975, the immigration of Lebanese nurses started to pose a significant problem to the health sector. In Lebanon, there is no official reporting of the exact number of practicing nurses or assessment of job satisfaction and retention. An unofficial report revealed that there are 3098 licensed nurses in Lebanon with a country population of around 3 million (LK Badr, unpublished data, 2000). There is variation in nurse staffing of hospitals in Lebanon. There is no standard system of allocating nurses to hospital beds or by acuity levels, nor is there a standard ratio of registered nurses (RNs) to practical and nurse aids. There are no unified levels of entry to the practice. There are many schools of nursing, most of them offering vocational training leading to the baccalaureate technique (BT) and technique superieur (TS). In addition, 6 universities offer bachelor of science (BS) or license in nursing. BT, TS, BS, and license holders are considered registered after passing the licensure government examination. In Lebanon, new hospitals and specialty centers are emerging that must recruit and retain sufficient numbers of nurses to meet present and future community health needs. Hence, despite much research into nurses’ job satisfaction, answers to important methodologic and conceptual questions continue to be obscure. Although the study findings may be specific to Lebanon, they can have relevance for the wider international nursing community.